DISCRETE-EVENT SIMULATION FOR SEMICONDUCTOR WAFER FABRICATION FACILITIES: A TUTORIAL - Fowler, John W.; Mönch, Lars; Ponsignon, Thomas (International Journal of Industrial Engineering: Theory, Applications and Practice, 2015)
Discrete-event simulation is a well-established and rather successful method in some semiconductor companies. while other companies do not use simulation at all. Simulation is used for performance assessment and decision-making. This paper focuses on the methodological and practical issues that have to be addressed to build, use, and maintain simulation models for a semiconductor wafer fabrication facility (wafer fab). We describe and discuss the main steps of a simulation study in this domain. We seek to highlight the main issues and present alternative ways to address them. Common pitfalls in using discrete-event simulation in semiconductor manufacturing and how they can be avoided are also discussed.